1988
DOI: 10.1161/01.atv.8.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Decreased coronary vascular reserve in Watanabe heritable hyperlipidemic rabbits.

Abstract: Watanabe heritable hyperlipidemic (WHHL) rabbits have severe hypercholesterolemia due to a genetic defect in their low density lipoprotein receptors. Therefore, they develop severe premature atherosclerosis of the large arteries including the coronary arteries. In the present study, we measured the coronary vascular reserve of these rabbits to evaluate the total cross-sectional coronary surface area. This method allowed us to quantify the functional consequences of the coronary atherosclerotic lesions. To eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the present study, we examined the atherosclerotic lesions of the left circumflex arteries (LCXs). The LCXs of rabbits have a greater diameter and length than those of the left anterior descending artery [4], and atherosclerotic lesions develop more frequently in the LCX than in the left anterior descending artery in WHHLMI rabbits [11, 22, 24]. …”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we examined the atherosclerotic lesions of the left circumflex arteries (LCXs). The LCXs of rabbits have a greater diameter and length than those of the left anterior descending artery [4], and atherosclerotic lesions develop more frequently in the LCX than in the left anterior descending artery in WHHLMI rabbits [11, 22, 24]. …”
Section: Methodsmentioning
confidence: 99%
“…Hypercholesterolemia induces microvascular dysfunction characterized by loss of endotheliumderived nitric oxide, increased rolling and adherence of leukocytes, and increased expression of P-selectin (10). Hypercholesterolemia also impairs coronary and aortic endothelium-dependent relaxation (EDR) in humans (5,24) and animal models (3,20,32). Previous studies showed that infarct size after coronary occlusionreperfusion is significantly larger in animals with acute or chronic hypercholesterolemia than in normal animals (11,15,18).…”
mentioning
confidence: 99%
“…Blood pressure was also monitored invasively at the femoral artery.. We analyzed the left circumflex artery (LCX) because it is a major coronary artery in rabbits [1, 13], and severe atherosclerotic lesions were observed in LCX; however, the degree of lesions was shown to markedly vary and the frequency of atherosclerotic lesions was low in the anterior descending artery [14]. …”
Section: Methodsmentioning
confidence: 99%